2021
DOI: 10.48550/arxiv.2109.00604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing triaxial deformation of atomic nuclei in high-energy heavy ion collisions

Jiangyong Jia

Abstract: Most atomic nuclei are deformed with a quadrupole shape described by its overall strength β2 and triaxiality γ. The deformation can be accessed in high-energy heavy-ion collisions by measuring the collective flow response of the produced quark-gluon plasma to the eccentricity ε2 and the density gradient d⊥ in the initial state. Using analytical estimate and a Glauber model, we show that the variances, ⟨ε 2 2 ⟩ or ⟨(δd⊥ d⊥) 2 ⟩, and skewnesses, ⟨ε 2 2 δd⊥ d⊥⟩ or ⟨(δd⊥ d⊥From these, we constructed several normal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…is the value for spherical nuclei with the reference radius and diffuseness, and b 1 -b 4 are centrality-dependent response coefficients that are encoded in the final-state dynamics. Note that the leadingorder contribution from deformation appears as β 2 n instead of β n because these observables do not depend on the sign of β n [20,34] 1 . The b n coefficients depend on the mass number but otherwise are the same between isobars.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…is the value for spherical nuclei with the reference radius and diffuseness, and b 1 -b 4 are centrality-dependent response coefficients that are encoded in the final-state dynamics. Note that the leadingorder contribution from deformation appears as β 2 n instead of β n because these observables do not depend on the sign of β n [20,34] 1 . The b n coefficients depend on the mass number but otherwise are the same between isobars.…”
mentioning
confidence: 99%
“…The first calculation is based on the quark Glauber model discussed in Refs. [20,34], where each nucleon is replaced by three constituent quarks. The distribution of quark-participants p(N quark ) generated for the parameter set of 96 Ru in Table I is then convoluted with a negative binomial distribution that describes the production of charged particle for each participant,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical estimation of shape and size are strongly correlated with nuclear deformation as illustrated in Ref. 52 So far, experimental measurements are limited to the mean transverse momentum and and its variance. [54][55][56][57][58] To save the computational overhead from loop-calculations, a framework for calculating the higher-order dynamical p T cumulants up to fourth-order using the standard and subevent methods is established and detailed in Ref.…”
Section: Transverse Momentum Fluctuationsmentioning
confidence: 99%
“…It is worth noting that the Cases 4-6 and the effect of β 3 have been studied in detail in Refs. [35,48,51], and their recent study suggested that the ratios calculated at the same N ch provide a better baseline for the non-CME background [52]. For simplicity, we choose the halo-type neutron skin case for doing our following study related to the CME.…”
Section: Introducing Geometry Configurations Of Isobar Nucleimentioning
confidence: 99%